Alcohol Dependence Is Associated with Blunted Dopamine Transmission in the Ventral Striatum - Martinez, Diana; Gil, Roberto; Slifstein, Mark; Hwang, Dah-Ren; Huang, Yiyun; Perez, Audrey; Kegeles, Lawrence; Talbot, Peter; Evans, Suzette; Krystal, John; Laruelle, Marc; Abi-Dargham, Anissa (Biological psychiatry (1969), 2005)
A decrease in dopamine type 2 receptors (D 2 ) and mesolimbic dopamine transmission predisposes animals to consume alcohol. This study measured D 2 receptors and dopamine transmission in human alcohol-dependent (AD) subjects using positron emission tomography (PET) and [ 11C]raclopride. Fifteen AD and 15 healthy control (HC) subjects were scanned before and after a psychostimulant challenge (amphetamine .3 mg/kg intravenous). The outcome measures for baseline D 2 receptor availability were binding potential (BP) and the equilibrium partition coefficient (V 3 ″). Amphetamine-induced [ 11C]raclopride displacement was measured as the difference in V 3 ″ between the two scans. [ 11C]raclopride BP was significantly reduced by 16.6% in the limbic striatum, 19.2% in the associative striatum, and 21.3% in the sensorimotor striatum in AD subjects compared with HC. The alcohol-dependent subjects showed a blunting of amphetamine-induced dopamine release in the limbic striatum: [ 11C]raclopride displacement was −5.2% ± 3.6% in AD subjects compared with −13.0% ± 8.8% in HC. However, no significant difference in [ 11C]raclopride displacement was seen in the associative (−4.6% ± 5.8% in AD subjects vs. −6.7 ± 5.4% in HC) and sensorimotor (−12.3% ± 7.3% in AD subjects vs. −13.7 ± 7.5% in HC) subdivisions of the striatum between the two groups. Alcohol dependence was associated with a decrease in D 2 receptors in each striatal subdivision, whereas amphetamine-induced dopamine release was reduced in the limbic striatum only.